Inter-dependent movements of Asiatic Cheetahs Acinonyx jubatus venaticus and a Persian Leopard Panthera pardus saxicolor in a desert environment in Iran (Mammalia: Felidae). Issue 4 (2nd October 2019) - Cheraghi, Farid; Delavar, Mahmoud Reza; Amiraslani, Farshad; Alavipanah, Kazem; Gurarie, Eliezer; Jowkar, Houman; Hunter, Luke; Ostrowski, Stephane; Fagan, William F.
Abstract : We investigated the simultaneous and sympatric movements of a coalition of two Asiatic Cheetahs ( Acinonyx jubatus venaticus) and a Persian Leopard ( Panthera pardus saxicolor), two rare and highly mobile large felids in Bafq Protected Area, Iran. The animals were tracked with GPS collars for 4.5 to 9 months at a temporal resolution of eight hours. The cheetahs used lower elevations areas (average: 1600 m), and remained more distant to the surrounding highways of (average: 14.5 km) than the leopard (average: 1.8 km and 12.3 km, respectively). The leopard's home range (408 km 2 ) was almost entirely within the larger home ranges of the cheetah coalition (1, 137 km 2 ). We found that the leopard approached more closely to either of the cheetahs in the rare occasions when they were separated, though whether that was the response of the cheetahs to the leopard or vice versa is unknown. This interaction eventually culminated in the leopard killing one of the cheetahs, the first documented proof of lethal competition between cheetah and leopard in Iran. The combined risks of larger home ranges beyond the protected areas with higher probability of encounters with humans, of highway crossing, and predation by Persian Leopards contribute to the particularly precarious situation of the Asiatic Cheetah.